The Role of ASEAN in Dispute Resolution between Thailand and Cambodia - Setyowati, Herning; Nurulita, Alma (Faculty of Law, Universitas Negeri Semarang, 2023)
This paper scrutinizes the Association of Southeast Asian Nations (ASEAN)'s involvement in mitigating the territorial and cultural disputes between Thailand and Cambodia, particularly centered on the contentious Preah Vihear Temple. The study assesses ASEAN's efficacy in resolving these disputes through diplomatic channels and mediation efforts. By analyzing ASEAN's mechanisms and diplomatic initiatives, the paper sheds light on the organization's role as a regional mediator in fostering peaceful resolution. ASEAN's engagement in the Thailand-Cambodia disputes reflects its commitment to the principles of conflict resolution and regional stability. Through mechanisms such as the ASEAN Regional Forum (ARF) and the ASEAN Way, ASEAN has provided platforms for dialogue and negotiation between the two nations. Additionally, ASEAN's efforts have included diplomatic interventions and initiatives aimed at de-escalating tensions and promoting mutual understanding. However, ASEAN's role in dispute resolution faces challenges stemming from complex historical grievances, power dynamics, and divergent national interests. The principle of non-interference, a cornerstone of ASEAN's approach, sometimes limits the organization's ability to intervene effectively in member states' internal affairs. Moreover, ASEAN's consensus-based decision-making process can impede swift action in resolving conflicts. Nevertheless, ASEAN's engagement in the Thailand-Cambodia disputes highlights the organization's potential as a regional peacemaker. By fostering dialogue, promoting confidence-building measures, and providing diplomatic support, ASEAN contributes to the maintenance of peace and stability in Southeast Asia. Through a comprehensive analysis of ASEAN's role in this specific context, this paper offers insights into the organization's capacity to address interstate conflicts and advance regional cooperation.